Adrenaline for the treatment of anaphylaxis: cochrane systematic review - Sheikh, A; Shehata, Y.A; Brown, S.G.A; Simons, F.E.R (Allergy, 2009)
Anaphylaxis is a serious allergic reaction that is rapid in onset and may cause death. Adrenaline is recommended as the initial treatment of choice for anaphylaxis. To assess the benefits and harms of adrenaline in the treatment of anaphylaxis. We searched the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library 2007, Issue 1), MEDLINE (1966 to March 2007), EMBASE (1966 to March 2007), CINAHL (1982 to March 2007), BIOSIS (to March 2007), ISI Web of Knowledge (to March 2007) and LILACS (to March 2007). We also searched websites listing ongoing trials: http://www.clinicaltrials.gov/, http://www.controlledtrials.com and http://www.actr.org.au/ and contacted pharmaceutical companies and international experts in anaphylaxis in an attempt to locate unpublished material. Randomized and quasi-randomized controlled trials comparing adrenaline with no intervention, placebo or other adrenergic agonists were eligible for inclusion. Two authors independently assessed articles for inclusion. We found no studies that satisfied the inclusion criteria. On the basis of this review, we are unable to make any new recommendations on the use of adrenaline for the treatment of anaphylaxis. In the absence of appropriate trials, we recommend, albeit on the basis of less than optimal evidence, that adrenaline administration by intramuscular injection should still be regarded as first-line treatment for the management of anaphylaxis.